Synthesis and Optical Characterization of Samarium Doped Cerium Fluoride Nanoparticles - Huong, Duong Thi Mai; Tien, Nguyen Thi; Vu, Le Van; Long, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics; Vol 31 No 4, 2015)
CeF 3 nanoparticles doped with 0; 1.0; 1.5; 2.0; 2.5; 3.0 and 4.0 mol% Sm 3+ were prepared by co-precipitation technique. These nanoparticles were studied by X-ray diffraction (XRD), transmission electron microscopy (TEM), photoluminescence (PL), photoluminescence excitation (PLE) spectra, energy-dispersive X-ray (EDS) and absorption spectra. The PL spectra exhibit a group of four emission lines, which are assigned to the transitions from the excited state 4 G 5/2 to the ground states 6 H J with J = 5/2; 7/2; 9/2 and 11/2 of Sm 3+ ion. The intensity of PL related to Sm 3+ ion reached to a maximum when the Sm dopant content was 2 mol%. The PLE spectra show 8 lines, which are attributed to the absorption transitions from the 6 H 5/2 ground state to the 4 H(1) 9/2 , 4 D(2) 3/2 , 6 P 7/2 , 4 F(3) 7/2 , 6 P 5/2 , 4 M 17/2 , 4 I(3) 13/2 and 4 M 15/2 excited states. Six lines among eight excitation lines were observed in the diffuse reflection spectra. Keywords: Co-precipitation, samarium doped cerium fluoride, nanopaticles, absorption, photoluminescence .